(untitled) (Academicia Globe: Inderscience Research, 2023)
The results of epidemiological studies conducted in the population of the Fergana Valley of Uzbekistan are presented. Based on the results of this work, which was carried out for the first time, a table for forecasting chronic obstructive pulmonary disease and an algorithm for early detection, as well as a medical-ecological cartography were developed and recommended for public use. Such activity reduces the "aggression" of this disease by 3 times. It dramatically increases the effectiveness of treatment and reduces the risk of pharmacotherapy up to 100.0 percent.